THE INFLUENCE OF SOCIAL MEDIA ON THE INTEREST OF GENTALA ARASY TOURISM VISITORS IN JAMBI CITY - Agesha Marsyaf; Firdaus Firdaus (Management Department, Faculty of Economics and Business, Universitas Jambi, 2022)
Social media provides information and communicates profiles, history, tourism, culinary, and various advantages of tourist destinations in our area. Along with developments, each region uses social media to introduce the area to the wider community. By paying attention to this need, we can find out the needs of the community for managing tourist accommodations to do a good image. Based on data on tourist attraction objects in Jambi City, the category of artificial tourism in 2019 in Jambi City is 62.25% , providing information that the existence of artificial tourism in Jambi City, which is located in Seberang City, can be enjoyed by tourists who want to know the development of Islamic history in Jambi City. Jambi Province and the history of the construction of the Gentala Throne Museum. It also has a pedestrian bridge which tourists can enjoy. Â